Trinigyrus spp. (Monogenea: Dactylogyridae) from Brazilian catfishes: new species, molecular data and new morphological contributions to the genus. (20th February 2020) - Franceschini, L.; Acosta, A.A.; Zago, A.C.; Müller, M.I.; da Silva, R.J.
Abstract: This study describes two new species, Trinigyrus anthus n. sp. and Trinigyrus carvalhoi n. sp., from gills of Hypostomus spp. from the Upper Paraná River basin, Brazil. Trinigyrus peregrinus is redescribed based on examination of its holotype, paratypes and new material of specimens parasitizing Pterygoplichthys ambrosettii, also from the Upper Paraná River basin, Brazil. New morphological features were included in the diagnosis of the genus, such as the presence of a sclerotized border on the anchor base, and a weakly sclerotized fringe on the base of the male copulatory organ (MCO). Trinigyrus anthus n. sp. differs from other congeners by the shape of the MCO, presenting an enlarged base with sclerotized fringes resembling flower petals. Trinigyrus carvalhoi n. sp. and T. peregrinus are similar but can be differentiated from each other mainly by the sclerotization of the vagina (absent in the new species), and the morphology of the MCO (C-shaped versus one counterclockwise circle, respectively). For the first time, gene sequences of Trinigyrus spp. from Brazil were obtained (partial ribosomal 28S and mitochondrial cytochrome c oxidase I (mtCOI)). The genetic divergences among the new species and T. peregrinus varied from 2 to 3% (6‒18 pb) based on sequences of 28S ribosomal DNA (rDNA), and 6–7% (83‒92 pb) using mtCOI. Phylogenetic analyses based on partial 28S rDNA revealed that Trinigyrus, Heteropriapulus and Unilatus formed a monophyletic and well-supported clade of monogeneans from Neotropical freshwater loricariids, suggesting a closer relationship among these dactylogyrids and their hosts.